The synthetic double wavelength technique: a simple robust method for thermodynamic temperature determination. (27th March 2020) - Briaudeau, Stéphan; Bourson, Frédéric; Kozlova, Olga; Sadli, Mohamed; Razet, Annick
Abstract: This paper describes a new relative technique developed at LNE-Cnam, for the determination of the thermodynamic temperature of blackbodies without recourse to a radiometric reference. This technique is referred to as the 'synthetic double wavelength technique' (SDWT) as it is considered to be a particular case of the 'double wavelength technique' (DWT). It offers a new experimental technique for the determination of the thermodynamic temperature at high temperature and as such a new means for the mise-en-pratique of the new definition of the kelvin achievable by any national metrology institute provided a multi-wavelength radiation thermometer combining large and narrow bandwidths is available. In this work, a first experimental implementation of this technique based on a wavelength-tuneable spectroradiometer providing both narrowband and broadband signals with the particularity of the broadband signal being virtually synthesised from the spectral distribution of the narrowband signals sampled over a wide spectral range. SDWT determination of the thermodynamic temperature of a blackbody at 2760 K was performed with a level of uncertainty that confirms the promising capabilities of this technique.